Visualization of the light interference process - Kolomoyets, D. A.; Nazarov, E. M. (ТДАТУ, 2020)
During this work, the knowledge gained in the study of physical laws and acquired skills in working with Blender Foundation software version 2.8 was consolidated. Using this version is free, simpler, allows you to create a more complex model of visualization of the physical process, the program runs on a PC.
Keywords: Foundation software version; complex model; visualization